Unveiling solidification mode transition and crystallographic characteristics in laser 3D-printed Al2O3-ZrO2 eutectic ceramics. (15th March 2022) - Fan, Zhiqi; Yin, Yu; Tan, Qiyang; Li, Xuliang; Niu, Pengda; Li, Ruidi; Yuan, Tiechui; Zhang, Ming-Xing; Huang, Han
Abstract: The crystallographic texture distribution in 3D-printed Al2 O3 -ZrO2 eutectics was found completely different from those prepared by directional solidification. The as-fabricated specimen was mainly composed of randomly oriented eutectic colonies, as a result of the initial uncoupled growth at molten pool boundaries. Specifically, the free-grown Al2 O3 faceted particulates in the uncoupled region acted as effective nucleation sites that triggered coupled eutectic renucleation and growth. Except for some misoriented ZrO2 precipitates in Al2 O3 matrix, well-defined multiple crystallographic orientation relationships existed between eutectic phases in the colony, e.g. 0001 A l 2 O 3 ∥ 100 Zr O 2 and 11 2 ¯ 0 A l 2 O 3 ∥ 100 Zr O 2 . The lattice matching change was attributed to the varied solidification conditions along the solid/liquid interface, as predicted by Jackson-Hunt model. Graphical abstract: Image, graphical abstract